Molecular evidence in identifying parents of Garcinia mangostana L. - Abdullah, Nur Ashikin Psyquay; Richards, A. J.; Wolff, K. (Universiti Putra Malaysia Press, 2012)
The obligate apomicts Garcinia mangostana L. (Clusiaceae) was described from Malaysia and hypothesized to have originated from the natural hybridization between G. malaccensis and G. hombroniana. One of the parents, i.e. G. malaccensis, was believed to be endemic in the state of Melaka. However, this was determined only through a comparison of their chromosome number and morphological characteristics. There is still the possibility of other species within the same section of G. mangotana as the possible parents. Thus, investigations were carried out using molecular markers from three different regions of the internal spacer, chloroplast and micorsatellite. The objective of this study was to identify the possible parents of G. mangostana by comparing its relationship to other species within the same section, based on the genetic analysis of the internal spacer, chloroplast and microsatellite regions. Meanwhile, comparisons of allele sizes between G. mangostana with G. malaccensis, G. opaca and G. hombroniana using six polymorphic primers which had previously been developed were also performed. For phylogenetic analysis ITS, trnL and accD-psaL primers were used to determine the relationships between the four Garcinia species in the Garcinia section with two other sections and the genus Clusia as an outgroup. From the genetic analysis, it was found that G. hombroniana shares no common allele with the other species, while G. opaca has similar allele sizes with G. mangostana and G. malaccensis. The phylogenetic tree also showed that the closest relative to G. mangostana is G. opaca and G. malaccensis. This proves that G. opaca is more likely to be the other parent of G. mangostana rather than G. hombroniana.